Determination of homeownership’s affordability in Penang - Azahar, Nurul Anis Syamimi (2024)
Nowadays, homeownership problem are critical due to higher of expenditures for the cost of living and housing cost. Majority of individual strunggling to owning a house especially for region that more urbanized and economically developed. This scenario lead to determine the affordability of homeownership in Penang. In this research, the single storey terrace house low cost choose as a case study to determine the affordability of homeownership.Therefore, there are three objectives of this research which are identify the affordability on factor for the homebuyers that successful owning a house , housing expenditures that must be paid by homeownership and analyze the homebuyer’s affordability using income ratio. For this method, the cost of housing must be less than 30% to be a affordability homebuyers. The research method have use is quantitative which is the data collected via the questionnaire through online and face to face The questionnaire have been constributed to 194 of sample size. Then, the data collected analyze in the Microsoft Excel to calculate the percentages of affordability and SPSS Version 29.0 for descriptive analysis. The findings shows majority of homebuyers are in affordability because ability owning a house at the age 27 years old without housing burden. The housing expenditures when owning a house are focus on loan repayment, housing utilities, property taxtion and other services. Lastly, hoped this research will assists individual to know the best affordability ratio when wanted to own a house and influence them to purchase a house at the working age.